Effect of Entrepreneurial Skills on the Performance of Small and Medium Sized Enterprises in Central Uganda: A Case Study in Luwero District - Hellen Birungi (Uganda Christian University, 2024)
This paper examines the effect of entrepreneurship skills training on the financial erformance of Small and Medium-Sized Enterprises in Luweero District, Uganda. Given the critical role that SMEs play in the process of economic development, especially employment creation and poverty reduction, this research examines the impact that specific competencies such as innovation, risk management, and communication have on growth and sustainability. This study will adopt a mixed-method approach to ascertain the impact that training in key entrepreneurial skills will have on financial performance from March 2024 to August 2024. The study will be geographically focused on selected SMEs in Luweero District. It is expected that the findings from this study will inform entrepreneurs, policy, and scholars with practical insights into how the effectiveness and competitiveness of SMEs can be enhanced. The literature review encompasses Innovation Theory by Schumpeter and Human Capital Theory, which addresses the underlying basis of innovation and acquired skills on which SME performances rely. Empirical studies conducted provide a platform upon which entrepreneurial training in innovation, risk management, and communication plays an integral part in financial success. The study also echoes the potential and contribution that entrepreneurship capability, including creative thinking, leadership, and teamwork, have for enhancing SME performance. This research goes on to outline areas not looked into, including defining creativity and measuring its direct impact on entrepreneurship. A cross-sectional research design entails stratified random sampling of 80 SMEs through the collection of quantitative and qualitative data. These indicate that creative thinking and leadership are the major drivers of SME performance, as depicted by both quantitative data from structured questionnaires and qualitative data from semistructured interviews. It is, therefore, conceivable to argue that the dissemination of entrepreneurial skills such as creative thinking and leadership increases SME performance in Luweero District, consequently contributing to regional economic development. Recommendations targeted at policymakers and business support organizations entail interventions and training programs that are intended to enhance SME performance.